Family Photography as Object and Practice in Independent Comics in Indonesia - Terra Bajraghosa; Budi Irawanto; Seno Gumira Ajidarma (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
One small element that is rarely put in the comics’ scene setting is photographic imagery, commonly a portrait of a person or a family photograph. It is assumed that once a family photograph is presented in a comic, it definitely has a particular function. This study will examine how the family photograph as an object and practice is depicted and present the signification of the story meaning in independent comics. The research object is a drawing that represents a family photograph in a panel, or series of panels – consecutive or non-consecutive -in the independent comic